Natural Resources, Investment and Long-Term Income - Dlisraios Papyrakis; Reyer Gerlagh (Fondazione Eni Enrico Mattei (FEEM), 2004)
We study the negative correlation between natural resource-abundance and long-term income focusing on the savings-investment channel. We first present empirical evidence on this channel and then develop an OverLapping-Generations (OLG) model to study the issue. In this model, savings adjust downwards to income from natural resources, and investment in capital contributes to knowledge creation, a feature based on endogenous growth theory. We analyze the link from resource income future income through savings and investment. Natural resources have two counteracting effects on income. In the short term, resource wealth augments income, but in the long-term, it decreases income through a crowding-out effect on capital and knowledge. We discuss different scenarios under which the resource curse is most likely to take place.
Keywords: E22; O13; 330; Natural resources; Growth; Investment; OLG models; Natürliche Ressourcen; Overlapping Generations; Endogenes Wachstumsmodell; Sparen; Investition